Design of constant output voltage DC-AC inverter for batteryless solar PV system - Agus Risdiyanto; Bambang Susanto; Noviadi Arief Rachman; Anwar Muqorobin; Tinton Dwi Atmaja; Harjono P. Santosa (Institute of Advanced Engineering and Science, 2020)
This paper introduces a DC-AC inverter design that operates stand alone to deliver power from solar photovoltaic (PV) to the load directly without going through the battery. In batteryless solar PV, the output voltage of solar PV always varies according to solar irradiation, temperature, so that it becomes a challenge in modelling DC-AC inverter with constant output voltage. The design consists of a boost converter, h-bridge switching and driver, and LC filter to generate sinusoidal ac voltage as output to load. To ensure a constant inverter output voltage, the design equipped by a close loop PI controller based on voltage control mode. The design modelled and simulated by PSIM. PV dc input was set variation according to the irradiation value (W/m2) and the output connected to a load that has rated voltage of 220 Vac and 3.4 A of nominal current. The results show that in the irradiation variation 600-1500 W/m2, the inverter was able to maintain the output voltage of 220 Vac ± 0.91%, 50 Hz which is still in the voltage range based on standard. The efficiency produced by DC-AC inverter 97.7% at 600 W/m2 and 83.6% at 1500 W/m2.